2003
DOI: 10.1039/b305296f
|View full text |Cite
|
Sign up to set email alerts
|

C–H and C–C agostic interactions in cycloalkyl tris(pyrazolyl)boratoniobium complexes

Abstract: H 11 (4),) have been prepared from Tp Me2 NbCl 2 (MeC᎐ ᎐ ᎐ CMe). The cyclopropyl complex 2a shows no sign of C-H agostic interactions either in the solid state (X-ray) or in solution. In contrast, the NMR spectra of 3 and 4 are temperature dependent as a consequence of an equilibrium between a major α-agostic species and a minor non-agostic one. Hybrid QM/MM calculations are used to rationalise the behaviour of these cycloalkyl species, and illustrate the subtle interplay of steric and electronic effects in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 59 publications
2
32
0
1
Order By: Relevance
“…In contrast, compared with free Binor-S (as determined from the structure of the tris-hydroxylated derivative [14] ), the CÀC bond that is in close proximity with the metal is lengthened by % 0.1 , whereas the two other CÀC bonds in the cyclopropane unit remain unchanged (Scheme 2). A similar, but slightly smaller, increase in CÀC bond length (0.049 ) has been noted in D. [6] The DFT calculated structure of 1 (see below; see Supporting Information for full details) is in close agreement with the experimentally determined structure, showing a lengthening of the C21ÀC25 bond (1.620 ), while the calculated CÀH bond lengths (1.104/1.105 ) are not significantly lengthened compared with the other calculated CÀH distances (cf. C24ÀH24 1.104 ).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In contrast, compared with free Binor-S (as determined from the structure of the tris-hydroxylated derivative [14] ), the CÀC bond that is in close proximity with the metal is lengthened by % 0.1 , whereas the two other CÀC bonds in the cyclopropane unit remain unchanged (Scheme 2). A similar, but slightly smaller, increase in CÀC bond length (0.049 ) has been noted in D. [6] The DFT calculated structure of 1 (see below; see Supporting Information for full details) is in close agreement with the experimentally determined structure, showing a lengthening of the C21ÀC25 bond (1.620 ), while the calculated CÀH bond lengths (1.104/1.105 ) are not significantly lengthened compared with the other calculated CÀH distances (cf. C24ÀH24 1.104 ).…”
supporting
confidence: 70%
“…The metal-mediated activation of carbon-carbon single bonds is the subject of significant contemporary interest, [1] with the putative intermediates in such processes being complexes in which the metal is bound through a CÀC s interaction. [2] Complexes showing such M···CC interactions are extremely rare, and are limited to intramolecular (agostic) interactions that have been reported for complexes A-D; [3][4][5][6] although in one case (A) the bonding mode has been queried. [7] The lack of well-characterized examples of such species is in contrast with M···HC agostic complexes that are well established; [2,[8][9][10] and further examples of genuine, fully-characterized examples of M···C À C s interactions are of clear importance regarding the fundamental study of CÀC activation processes.…”
mentioning
confidence: 99%
“…[112][113][114] In 1992, Tilley et al had already suggested that "a transient intermediate which may form prior to a four-center transition state is a complex with coordinated SiÀH, HÀH, or Si À Si s bonds." [115] There are now a few examples of C À C agostic complexes, [65,[116][117][118][119][120] but intermolecular s-C À C complexes are not known as far as we are aware. We look forward to the discovery of evidence for s-EÀE' complexes and their reactivity.…”
Section: Methodsmentioning
confidence: 96%
“…Milstein and colleagues have characterized a number of PCP-and PCN-type rhodium pincer complexes (e.g., Scheme 2, complexes III) in solution that are proposed to have agostic M⅐⅐⅐C-C interactions on the basis of NMR data and a solid-state structure that shows a closer than van der Waals separation between Rh and C(2, [33][34][35]. Etienne and colleagues have described the niobium cyclopropyl complex IV that shows a close Nb⅐⅐⅐C-C contact and lengthening of the C-C distance in the cyclopropyl group consistent with an agostic C-C⅐⅐⅐Nb interaction (36,37). An early report of an agostic C-C complex recently has been reassessed by Maseras and Crabtree (38) as one that has a close nonbonding contact with a C-C bond and not an agostic species.…”
mentioning
confidence: 99%